Multi-trait analysis of post-harvest storage in rocket salad (Diplotaxis tenuifolia) links sensorial, volatile and nutritional data. (15th November 2016) - Spadafora, Natasha D.; Amaro, Ana L.; Pereira, Maria J.; Müller, Carsten T.; Pintado, Manuela; Rogers, Hilary J.
Highlights: Volatile organic compounds changed with sensorial quality over time and temperature. Changes in VOCs could act as markers for post-harvest loss of vitamin C content. A rise in sulphur containing VOCs was an indicator for increased microbial counts. Abstract: Rocket salad ( Diplotaxis tenuifolia ; wild rocket) is an important component of ready to eat salads providing a distinct peppery flavour and containing nutritionally relevant compounds. Quality deteriorates during post-harvest, in relation to time and storage temperature amongst other factors. Volatile organic compounds (VOCs) are easily measurable from rocket leaves and may provide useful quality indicators for e.g. changes in isothiocyanates derived from nutritionally important glucosinolates. VOC profiles discriminated storage temperatures (0, 5 and 10 °C) and times (over 14 days). More specifically, concentrations of aldehydes and isothiocyanates decreased with time paralleling a fall in vitamin C and a reduction in sensorial quality at the two higher temperatures. Sulphur containing compounds rise at later time-points and at higher temperatures coincident with an increase in microbial titre, mirroring a further drop in sensorial quality thus indicating their contribution to off-odours.